EARLY DETECTION OF CHANGES IN BLOOD GLUCOSE LEVELS AS AN EFFORT TO INCREASE SUCCESS FOR THE TREATMENT OF LUNG TUBERCULOSIS - Pariyana Pariyana; Iche Andriyani Liberty; Eka Febri Zulissetiana (Majalah Kedokteran Sriwijaya, 2020)
Tuberculosis (TB) is a pulmonary infectious disease which is the main cause of increased morbidity and mortality worldwide. Diabetes mellitus is one of the factors that can increase the incidence of pulmonary tuberculosis. This study aims to determine changes in glucose levels in pulmonary TB patients at the beginning of being diagnosed with pulmonary TB or before receiving OAT therapy and after receiving OAT therapy. This study is an analytical study with a cross-sectional repeated measurement design, namely measuring blood glucose levels repeatedly for 2 times (the initial measurement of treatment before receiving OAT therapy and measurement after receiving OAT therapy). The sample in this study were 107 pulmonary tuberculosis patients who were treated at the Public Health Center in Palembang City. The sampling technique is proportional random sampling. Data analysis in this study was carried out descriptively and analytically using the t-test (Wilcoxon). The results showed that in TB patients with normal initial glucose level status, there was a significant difference in glucose levels before and after receiving OAT therapy (p-value = 0.000) p <?, TB patients experienced binding of glucose levels after receiving OAT therapy while in TB patients with DM status, showed no significant difference in glucose levels before and after receiving OAT therapy (p-value = 0.135) p> ?.